Far-infrared ray patches relieve pain and improve skin sensitivity in myofascial pain syndrome: A double-blind randomized controlled study. (December 2017) - Lai, Yen-Ting; Chan, Hsiang-Lin; Lin, Shu-Huan; Lin, Chih-Ching; Li, Szu-Yuan; Liu, Chih-Kuang; Teng, Hao-Wei; Liu, Wen-Sheng
Highlights: Myofascial pain syndrome (MPS) is one of the most common causes of musculoskeletal pain. The prevalence of MPS is predicted to be 12% in general population. The best treatment for MPS is still in debating. Noninvasive or invasive treatments both have disadvantages; while far-infrared ray (FIR) patch is easy to applied and safe. There are totally 201 trigger points. 189 completed the study. We randomized patients into two groups: intervention group with FIR patches for 24 hours, while control group with mask patches. After the intervention, both groups are significantly improved in pain score (V), but only patients in the study group with FIR patches showed better skin sensitivity with lower pain threshold (P) and tolerance (T). The skin sensitivity in women is better than men due to thinner skin. Also the skin sensitivity is decreased with age, which can be improved by FIR patches. Abstract: Objective: Myofascial pain syndrome (MPS) is a common disorder characterized by muscle pain if myofascial trigger points (MTrP) are stimulated. This study evaluated the effectiveness of far-infrared ray (FIR) patches in reducing the severity of pain in patients with MPS. Methods: A double-blind, randomized controlled study involving 125 patients with MPS and 201 MTrPs located in the trapezius muscle. A FIR patch was applied to 98 MTrPs for 24 h in the intervention group (61 patients) and a placebo patch was applied to 91 MTrPs in the control group (57 patients) at the end. Pain intensity was measured using the visual analogue scale (V) while pressure pain threshold (P) and maximal pain tolerance (T) were measured using an algometer before and after treatment. Results: The mean age of the patients was 37.16 years old and 67% were female. There was a positive correlation between P and T ( p < 0.001). Older Age was associated with higher P and T due to poor skin sensitivity ( p < 0.001). V improved significantly in both groups to a similar extent, but only in the intervention group, P and T decreased significantly (which implied better skin sensitivity) ( p < 0.05). P and T decreased the most in the female group aged over 35, probably due to thinner skin in this subgroup. Conclusions: FIR and placebo patches were equally effective at relieving pain (with decreased V), but P and T dropped only in the intervention group with FIR patches. This probably resulted from FIR penetrated only to the skin layer and improved skin sensitivity with more blood circulation, but the muscle remained unaffected. Further studies should investigate the effect of longer exposure or higher energy applications.